2002
DOI: 10.1046/j.1468-2982.2002.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Magnesium Sulphate in the Acute Treatment of Migraine Without Aura and Migraine with Aura. A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Magnesium sulphate has been used in the acute treatment of migraines; some studies found it to be a highly effective medication in the acute control of migraine pain and associated symptoms. This randomized, double-blind, placebo-controlled study assesses the effect of magnesium sulphate on the pain and associated symptoms in patients with migraine without aura and migraine with aura. Sixty patients in each group were assigned at random to receive magnesium sulphate, 1000 mg intravenously, or 0.9% physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
120
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(121 citation statements)
references
References 27 publications
1
120
0
Order By: Relevance
“…Decreased Mg 2+ concentrations also can activate NMDA receptors and, thus, can increase neuronal excitability. In agreement with this hypothesis, the infusion of Mg 2+ provided sustained headache relief (Bigal et al 2002), and oral Mg 2+ has been demonstrated to be an effective prophylactic in menstrual migraine (Facchinetti et al 1991). Thus, glutamate receptor modulators seem to be of benefit in migraine treatment; indeed, the NMDA receptor antagonist memantine and the NR2B subunit containing antagonist, CP-101,606, decreased spreading depression (Peeters et al 2007), a potentially important factor in migraine pathophysiology.…”
Section: Glutamate Receptorsmentioning
confidence: 80%
“…Decreased Mg 2+ concentrations also can activate NMDA receptors and, thus, can increase neuronal excitability. In agreement with this hypothesis, the infusion of Mg 2+ provided sustained headache relief (Bigal et al 2002), and oral Mg 2+ has been demonstrated to be an effective prophylactic in menstrual migraine (Facchinetti et al 1991). Thus, glutamate receptor modulators seem to be of benefit in migraine treatment; indeed, the NMDA receptor antagonist memantine and the NR2B subunit containing antagonist, CP-101,606, decreased spreading depression (Peeters et al 2007), a potentially important factor in migraine pathophysiology.…”
Section: Glutamate Receptorsmentioning
confidence: 80%
“…[8][9][10] One double-blinded randomized, placebo-controlled trial also showed impressive benefits of IV magnesium in a subgroup of 30 patients suffering migraine with aura. 11 Only one study that failed to show benefit of IV magnesium has been published, although magnesium was used in addition to metoclopramide in this study. 12 So an uncritical review of the prior literature would suggest that IV magnesium is beneficial in migraine and other benign headaches.…”
Section: Best Evidence?mentioning
confidence: 98%
“…Magnesium sulphate was effective in a small placebo-controlled trial (Demirkaya et al, 2001 Level II), with another trial demonstrating a reduction in all of the symptoms of migraine with aura (including headache), but only in photo/phonophobia in migraine without aura (Bigal, Bordini, Tepper et al, 2002 Level II). However, other studies showed that a combination of magnesium and metoclopramide was less effective than metoclopramide plus placebo (Corbo et al, 2001 Level II) and there was no significant difference between magnesium, metoclopramide or placebo (Cete et al, 2005 Level II).…”
Section: Other Drug Treatmentsmentioning
confidence: 99%